Analisis Multilevel pada Ketidaklayakan Upah Pekerja Perempuan Usia 18–49 Tahun pada Sektor Tersier di Nusa Tenggara Barat Tahun 2023 - Mauboy, Lourna Mariska; Sitorus, Jeffry Raja Hamonangan (Politeknik Statistika STIS, 2025)
Unlivable wages remain a key challenge in development. Despite minimum wage policies, many workers, especially women, still earn below the standard. West Nusa Tenggara (NTB) records the lowest average wage for female workers in Indonesia, even within the tertiary sector, which contributes the highest output and is the main employment source for women. This study examines unlivable wages among female tertiary-sector workers aged 18–49 using multilevel binary logistic regression with random intercept. Results show that 78.44% of women in this group still receive unlivable wages. Significant individual factors include child ownership, education level, certified training, and weekly working hours. At the regional level, the Open Unemployment Rate (OUR) is influential. These findings suggest that wage policy should consider both individual and regional aspects to improve wage livability for female workers in NTB’s tertiary sector.